Human embryonic research: the Malaysian regulatory framework, human fertilization and embryology Act 1990 (United Kingdom) and shariah perspective - Fadilah binti Abd. Rahman (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2011)
Today, human embryo has tremendously become one of the important subjects of research and experimentations. The research is regarded as very important in developing solutions for the treatment and prevention of infertility and other diseases or disorders in human. However, the field of embryo research has been followed by ethical, religious and legal controversies from the very beginning and these issues have been crucial in many decision-making. This study provides an analysis of the medicar and legal aspects of research using human embryo under the UK and Malaysian regnlatory framework. Shariah perspective on this topic is also comprehensively discussed as it is deemed to be indispensable especially in a country like Malaysia which gives special status to Islam as the official religion. This study principally seeks to answer FIVE (5) fundamental questions, namely: First: the extent to which UK legislations on embryo ·research or its precedent should be likely to be adopted by the Malaysian Legislature and courts, Second: the adequacy of the Malaysian regulation in regulating research activities involving human embryo, Third: the extent of desirability of regulating specific legislation on human embryo research among the local medical practitioners and scientists, Fourth: the extent to which the practice and research using human embryos would be accepted from the Islamic perspectives, and Fifth: the extent to which Islamic perspective should influence the Malaysian Legislature in the making of future legislation. The Malaysian regulatory framework concerning embryo research is not comprehensive and incomplete. There exist uncertainties, inadequacies, and inconsistencies in the existing guidelines relevant to research using human embryo, and the absence of adequate and effective controlling and monitoring system. These findings have led to the conclusion that, in order to effectively regulate research activities using human embryos, Malaysia need a model to follow. In relation to that, it is also the finding of this study that the UK experiences in determining the policy for, and in legislating embryo research has been proven to be of assistance in guiding Malaysia towards determining its own policy. The HFE Act 1990 in particular, has also provided useful guidelines for Malaysia in ascertaining the relevant provisions to be incorporated in Malaysian future legislation concerning embryo research. Study conducted on the general and specific comments and criticisms made to the Act have indeed been of help in pointing out certain important areas of the Act that need proper consideration and attention from Malaysia. With regard to the extent to which UK approach and its legislation should be likely to be adopted by the Malaysian Legislature, it has been proven by this study that the Islamic framework has proven to be of useful 'evaluating tool' in drawing up the limit of adoption. As such, it has become possible to determine the position of the HFE Act 1990 provisions from the Islamic point of view. Despite the popularly claim that the UK legislation is of a liberal one, it is apparent from this study that the provisions contained in the Act concerning embryo research are largely in concordance with the Islamic framework, except on few matters. In reliance to these conclusions, some recommendations considered as fundamental and pertinent to legislating embryo research in Malaysia have also been made. The recommendations addressed are meant not only to national policy-makers and scientific investigators, but also public and private research institutions, fertility centers, patients and wider communities.